TINJAUAN YURIDIS PERKARA PERDATA DAN PIDANA TENTANG KEABSAHAN PERKAWINAN TERHADAP PUTUSAN PENGADILAN NEGERI KEDIRI - Tontowi (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2022)
With the development of technology that is able to penetrate all corners of the country, it also indirectly provides community learning in all respects. From the development of customs and culture in the West, if there is a case of domestic dispute, then what happens is to ask for compensation. If there is a slight problem, then the thought is to concoct the problem to be improved in legal remedies. The legal research method used is juridical-normative, meaning an approach based on applicable laws and regulations, and is related to decisions related to the material discussed based on the deductive method, which is a process of thinking by drawing special conclusions from a general reality The legal source used in this study is that two data are used, namely primary data and secondary data, meaning that primary data includes laws and regulations related to legal issues written. The results showed that the Marriage Law Number 1 of 1974, in its implementation there is a Government Regulation Number 9 of 1975, and a Presidential Instruction and Decree of the Minister of Religious Affairs. So that the Islamic Law referred to in this writing is what is contained in the Presidential Instruction and Decree of the Minister of Religious Affairs which is hereinafter referred to as the